Reflections on the social dialogue in Poland preparing to the EU accession (Contemporary Central & East European Law, 2002)
Article is about Social Dialogue in Poland on topic of accession to EU. Polish social opinion change dramatically between years 1994 and 2001. Supporters of accesion decreased and people who are against it rose. Animosity between two main polish work trade unions OPZZ and Solidarity made problems for Goverment steps to entry Poland to the UE commonwealth.